2002
DOI: 10.1002/jmri.10125
|View full text |Cite
|
Sign up to set email alerts
|

Applications of neural network analyses to in vivo 1H magnetic resonance spectroscopy of Parkinson disease patients

Abstract: Purpose: To apply neural network analyses to in vivo magnetic resonance spectra of controls and Parkinson disease (PD) patients for the purpose of classification. Materials and Methods:Ninety-seven in vivo proton magnetic resonance spectra of the basal ganglia were recorded from 31 patients with (PD) and 14 age-matched healthy volunteers on a 1.5-T imager. The PD patients were grouped as follows: probable PD (N ϭ 15), possible PD (N ϭ 11), and atypical PD (N ϭ 5). Total acquisition times of approximately five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 30 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…Consequently, the combinatorial explosion due to the large number of features was effectively prevented when using the dynamic programming-based feature extraction. Note that data processed by our technique may be used in connection with any other optimization technique such as a genetic algorithm for feature extraction or other classification techniques, including neural networks [11], support vector machines etc. It may be also used as a preprocessing step for more sophisticated dimension reduction techniques [12].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the combinatorial explosion due to the large number of features was effectively prevented when using the dynamic programming-based feature extraction. Note that data processed by our technique may be used in connection with any other optimization technique such as a genetic algorithm for feature extraction or other classification techniques, including neural networks [11], support vector machines etc. It may be also used as a preprocessing step for more sophisticated dimension reduction techniques [12].…”
Section: Discussionmentioning
confidence: 99%
“…Axelson and colleagues have developed an interesting alternate approach to the analysis of spectroscopic data based on pattern recognition with an artificial neural network [29]. These investigators reported that, while conventional data analysis, i.e., estimation of metabolite ratios from peak area measurements, showed no significant abnormalities in PD, trained neural networks could distinguish control from PD spectra with considerable accuracy.…”
Section: Parkinson_s Disease and Related Disordersmentioning
confidence: 98%
“…[12]), were used to train the RBFNN. [12] where the Lorentzian peak is defined as, [13] and the Gaussian peak is defined as,…”
Section: Quantification With Rbfnnmentioning
confidence: 99%
“…Such a goal could possibly be realized using methods based on artificial neural networks (ANN). The ability of ANN for classification of spectra for various pathologies has been demonstrated [6][7][8][9][10][11][12][13][14]. However, relatively little attention has been paid to metabolite quantification using ANN [15][16].…”
Section: Introductionmentioning
confidence: 99%